A case study of tri-morbidity. Issue 3 (10th August 2020) - Player, Emily; Clark, Emily; Gure-Klinke, Heidi; Walker, Jennifer; Steel, Nick
Abstract : Purpose: The purpose of this paper is to highlight the vulnerability of individuals living with tri-morbidity and the complexity of care required to serve this patient group, moreover to consider how a life course approach may assist. Design/methodology/approach: This paper uses a case study of a death of a young male adult experiencing homelessness and tri-morbidity in the UK and comparison of the mortality data for homeless adults in the UK with the general population. A synopsis of the mental health and health inclusion guidance for vulnerable adults is used. Findings: This paper found the importance of considering a life course approach and the impact of negative life events on individuals living with tri-morbidity and also the role of specialist services to support the complex needs of vulnerable adults including the importance of multi-disciplinary working and holistic care. Research limitations/implications: The research implications of this study are to consider how individuals living with tri-morbidity fit in to evidence-based care. Practical implications: The practical implication is to consider that those living with tri-morbidity have extra-ordinary lives often with a high concentration of negative life events. Therefore, an extra-ordinary approach to care maybe needed to ensure health inequalities are reduced. Social implications: This paper is an important case highlighting health inequalities, specifically mortality, in the homeless population. Originality/value: This paper is an original piece of work, with real cases discussed but anonymised according to guidance on reporting death case reports.